2015
DOI: 10.1177/0733464815614918
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Older Adults on Waiting Lists for Meals on Wheels: Identifying Areas for Intervention

Abstract: The purpose of this study was to characterize the population of seniors on Meals on Wheels’ (MOW) waiting lists and identify their rate of depression, anxiety, falls, and fear of falling. Data come from surveys of 626 seniors on waiting lists across the country and the 2013 National Health and Aging Trends Study (NHATS). Results suggest that seniors on waiting lists for MOW were more likely to be widowed, less educated, older, Black, Hispanic, and receive Medicaid than the population of community-dwelling olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
1
15
0
2
Order By: Relevance
“…Three programs were highlighted below and examined in the current study: (1) the village program with neighbors help neighbors grassroots network, (2) the neighborhood lunch program (i.e., congregate meals) authorized under Title III of the Older Americana Act to provide meals and nutritional services in group settings ( Lloyd & Wellman, 2015 ; Mabli et al, 2015 )., and (3) University-based lifelong learning programs meeting the learning and social engagement needs ( American Council on Education, 2007 ). These programs represent different AIC options for community-dwelling older adults with different demographic and background characteristics ( Hou, 2019b ; Thomas et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three programs were highlighted below and examined in the current study: (1) the village program with neighbors help neighbors grassroots network, (2) the neighborhood lunch program (i.e., congregate meals) authorized under Title III of the Older Americana Act to provide meals and nutritional services in group settings ( Lloyd & Wellman, 2015 ; Mabli et al, 2015 )., and (3) University-based lifelong learning programs meeting the learning and social engagement needs ( American Council on Education, 2007 ). These programs represent different AIC options for community-dwelling older adults with different demographic and background characteristics ( Hou, 2019b ; Thomas et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that neighborhood lunch program (NLP) participants were mostly older adults with diverse racial and income levels ( Brewer et al, 2016 ; Thomas et al, 2017 ). Older adults participating in university-based lifelong learning programs (LLP) are more likely to be white and have higher education ( Park et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the clients of unsatisfied of MOW were at risk of malnutrition or malnourished and depressive more often than the clients of satisfied of MOW. Earlier studies have documented rates of depression among older adults currently receiving in-home services [24]. Lack of appetite, loss of interest in self-care, apathy and physical weakness can be used early warning signals not only the risk of malnutrition or malnutrition, also depression [25].…”
Section: Factors Associated With the Use Of Meals-on-wheels Among Hommentioning
confidence: 99%
“…The complexity of developing solutions to diverse, emerging forms of need highlights knowledge gaps in the literature on food and nutrition assistance to seniors. Much of the research on this topic to date documents the impacts of home-delivered and congregate meals on psychosocial and physiological outcomes (e.g., Campbell et al, 2015; Kretser et al, 2003; Sharkey, 2003; Thomas et al, 2017). Research has also focused on SNAP, food insecurity, and health outcomes among seniors (e.g., Gundersen & Ziliak, 2015; Samuel et al, 2018; Srinivasan & Pooler, 2018; Szanton et al, 2017).…”
Section: Introductionmentioning
confidence: 99%